Performances of Crossbred Chickens Fed Fermented Papaya Leaf and Seed Powder at High Stocking Density - S. Sugiharto; T. Yudiarti; E. Widiastuti; H. Wahyuni; T. Sartono; A. R. Pratama (Tropical Animal Science Journal, 2021)
The study evaluated the influence of fermented papaya leaf and seed powder (FPLS) and/or multienzymes on the growth, physiology, antioxidant, and gut ecology of the Indonesian crossbred chicken (ICC) at high stocking density. Three hundred and seventy ICC were randomly allotted to LSD (chicks fed conventional feed at low stocking density), HSD (chicks fed conventional feed at high stocking density), HSD+mE (chicks fed conventional feed plus multienzyme at high stocking density), HSD+FPLS (chicks fed FPLS at high stocking density) and HSD+FPLS+mE (chicks fed FPLS plus multienzyme at high stocking density). Body weight and feed intake were determined weekly. Two ICC were taken from each pen (10 chicks per treatment group) at week 10 for sampling. The study was arranged based on a completely randomized design with five treatment groups, each consisted of five replicates. Except for performance, analysis of variance was conducted on two chicks from each replicate (10 chicks per treatment group). Chicks in LSD consumed more (p<0.05) feed and had a higher (p<0.05) feed conversion ratio. Platelet distribution width (PDW) was lower (p<0.05) in HSD, HSD+FPLS, and HSD+FPLS+mE chicks than in LSD chicks. Lymphocyte counts were lower (p<0.05) in HSD relative to HSD+mE chicks. Superoxide dismutase (SOD) was higher (p<0.05) in HSD and HSD+FPLS+mE chicks than in LSD, HSD+mE, and HSD+FPLS chicks. High-density lipoprotein was smaller (p<0.05) in HSD+mE chicks than in LSD, HSD, and HSD+FPLS chicks. Compared to the other treatment groups of chicks, HSD+FPLS chicks had a lower (p<0.05) albumin level. Creatinine level was lower (p<0.05) in HSD chicks than in the other group of chicks. Enterobacteriaceae counts were lower (p<0.05) in HSD+FPLS cecal content of chicks than in LSD and HSD chicks. The redness values of breast meats were lower (p<0.05) in HSD+FPLS chicks than the chicks in HSD+mE and HSD+FPLS+mE dietary treatments. LSD chicks had higher (p<0.05) redness values of thigh meat than the other treatment groups of chicks. LSD chicks also had higher (p<0.05) yellowness values than HSD+mE and HSD+FPLS+mE chicks. In conclusion, high stocking density resulted in mild stress conditions, as was demonstrated by the increased SOD and decreased PDW and redness meat values. A combination of FPLS and multienzyme ameliorated the adverse influence of high stocking density in ICC.